CALIDAD DE VIDA DE LOS ADULTOS MAYORES EN LA COMUNIDAD EL RODEO CANTON OÑA PROVINCIA DEL AZUAY Y LA INTERVENCION DEL TRABAJADOR SOCIAL. - Solano Solano, Dolores Margarita (2015)
The research was applied in the community "El Rodeo" Oña Canton, Azuay Province, through a preliminary survey in which relative neglect of older adults who suffer daily the lack of love and companionship of loved ones was determined, is a dynamic that exists every day, there are countless stories exist about the abandonment, displacement or exile of the family, stories that describe the reality of the elderly. This work had as general objective to investigate how the abandonment affects the quality of life of seniors, it was achieved through the specific objectives in which the causes and consequences are determined and theoretically support related categories: adult greater, neglect, quality of life and social work intervention. Similarly a proposal for action to improve the quality of life of the elderly, through the operation of a recreational center was developed. The method from the abstract to the concrete was used for the research process, through the model of intervention in reality with their respective levels and stages that allowed deconstruct the problem. Also, as the survey instrument was structured and applied to a sample of 25 seniors. Migration and widowhood: In the main findings from field research, fuzzy factors affecting the abandonment as it was discovered. In addition, family abandonment has affected mainly the emotional, moral suffering from various disorders, loneliness and depression, which lead to feel unprotected by lack of attention, love and care of their families. The replies received from the survey confirmed the enthusiasm and positive attitude that adults have to attend recreation. In conclusion, this study demonstrated that we need a recreation center is very important to improve the quality of life of older adults through 5 recreational activities that will strengthen the psychological emotional, physical well-being of these people.